Computer-Based Methods for Promoting Thinking in Physics and Algebra Incorporating Cognitive Research Findings into Software Design - Mestre, Jose P.; Massachusetts Univ., Amherst. Dept. of Physics and Astronomy ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
The increasing availability of the computer in the classroom has created a need for informed and creative instructional software. Two areas of cognitive research in mathematics and science learning have implications to instruction and, consequently, to educational software design. These are research on misconceptions and on differences between expert and novice problem solvers. This paper treats these areas in two major sections. The first section provides a broad overview of the misconception literature and of the instructional implications associated with this body of research. Also included in the first section is a description of a computer-based approach designed to teach students how to translate algebraic word problems into equations. The second major section provides an overview of the differences between experts and novices and discusses a computer-based approach in which students are constrained to analyze physics in expert-like ways. The computer-based example used relates to the analysis of classical mechanics problems. A 31-item list of references concludes the document. (TW)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Sponsoring Agency: National Science Foundation, Washington, DC.
Contract Number: 400-81-0027.
Contract Number: BNS-811109.
Contract Number: G-79-0024.
ERIC Note: Paper presented at the International Conference on Thinking (3rd, Honolulu, HI, January 4-8, 1987). Figures contain small print.
Keywords: Algebra; College Mathematics; College Science; Courseware; Higher Education; Mathematics Education; Mathematics Instruction; Misconceptions; Physics; Problem Solving; Science Education; Science Instruction; Secondary Education; Secondary School Mathematics; Secondary School Science; Reports, Descriptive; Reports, Research; Speeches/Meeting Papers